2019
DOI: 10.1007/s40415-019-00537-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical changes in cherry tomato plants caused by boron deficiency

Abstract: Boron is one of the micronutrients that mostly limits crop yield in Brazil, especially for tomato. When boron is deficient, there is initially growth reduction in meristematic tissues (root ends and branches), although for tomato, this behavior has not yet been characterized. The aim of this work was to characterize the effects of boron deficiency on biometric characteristics, anatomical changes and deficiency symptoms in cherry tomato plants. For this, cherry tomato plants of cultivar Sindy were cultivated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…B deficiency causes disruption in pectate deposition and middle lamella formation. It also causes rapid hardening of the cell wall, controlling the arrangement of the microfibrils of xyloglucans and cellulose, which does not allow a normal increase in cell volume, limiting cell division and differentiation, primarily in meristematic tissues (Mengel and Kirkby 2001;Liu et al 2014). The height growth of the plant is also impaired since B has a direct effect on the formation of xylem vessels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…B deficiency causes disruption in pectate deposition and middle lamella formation. It also causes rapid hardening of the cell wall, controlling the arrangement of the microfibrils of xyloglucans and cellulose, which does not allow a normal increase in cell volume, limiting cell division and differentiation, primarily in meristematic tissues (Mengel and Kirkby 2001;Liu et al 2014). The height growth of the plant is also impaired since B has a direct effect on the formation of xylem vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The main known function of this micronutrient is related to the synthesis, constitution and regulation of cell walls and membranes, which characterizes its structural function and insignificant phloem redistribution (Bolaños et al 2004). B deficiency in plants primarily causes metabolic, morphological and anatomical changes (Liu et al 2014;Milagres et al 2019), then it results in symptoms at morphological level, which also compromises fruit yield and most of fruit quality (White and Broadley 2003;Fontes 2011). Because of the rapid development of tomato and the low transpiration rate of buds and fruits compared with leaves (Kinet and Peet 2006), the lack of B is responsible for the disruption and death of the meristematic tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When in boron-deficient conditions, plants have reduced photosynthetic capacity, thereby preventing cell division and development in chickpea plants [15]. Boron promotes the absorption of calcium and increases the content of vitamin C in the fruit by improving membrane integrity, slowing biosynthesis and reducing respiration in cherry tomato [16]. Davis et al [17] found leaf sprays of boron increased shelf life of tomato fruit.…”
Section: Introductionmentioning
confidence: 99%